Company Value: Carbon Emission Disclosure, Company Size, and Profitability With Environmental Performance As a Moderating Variable - Mahardian Hersanti Paramita; Wiralestari Wiralestari; Nela Safelia (Pt. Anagata Sembagi Education, 2025)
This study aims to determine the effect of carbon emission disclosure, company size, and profitability on firm value, with environmental performance as a moderating variable. The population of this study was companies in the energy sector and the primary consumer goods industry listed on the Indonesia Stock Exchange (IDX) in 2020–2022. The sample used a purposive sampling technique, with a final sample size of 114 companies. This research method uses a quantitative method with secondary data in the form of annual reports and company sustainability reports. The results show that carbon emission disclosure has a positive effect on firm value. Company size has a positive effect on firm value. Profitability has a positive effect on firm value. Environmental performance can moderate the influence of CED, company size, and profitability on firm value.